A case report and a literature review of double mammary pseudoangiomatous stromal hyperplasia associated with galactoma during pregnancy - Yu, Minmin; Shi, Guangxi; Gao, Zong; Wu, Kai; Wei, Cuilei; Li, Xiaohong; Miao, Xiuming (Frontiers in Oncology, 2024)
Pseudoangiomatous stromal hyperplasia (PASH) is a benign interstitial hyperplasia of the breast that usually occurs in premenopausal or perimenopausal women. It is usually characterized by localized lesions or clear boundary masses, and diffuse double breast enlargement is rare. PASH is considered a hormone-dependent disease that is commonly progesterone related. There are no imaging characteristics, and both benign and suspicious malignant signs can be seen. The definitive diagnosis of PASH depends on a pathological diagnosis, and it is necessary to be vigilant in distinguishing between benign and malignant tumors with similar breast histopathology. Here, we report the case of a 23-year-old multipara patient with bilateral diffuse pseudoangiomatous stromal hyperplasia of the breast during pregnancy who presented with macromastia and reviewed the literature to further understand the clinical features, pathological diagnosis, differential diagnosis, treatment and prognosis of pseudoangiomatous stromal hyperplasia of the breast.